Supervisory Control and Data Acquisition System (SCADA) in Construction Industries: Implementing SCADA technology for efficient construction management (Journal of Advances and Scholarly Researches in Allied Education, 2018)
SCADA technology provides a thorough understanding of the fundamental concepts and the practical issues of SCADA systems. Particular emphasis has been placed on the practical aspects of SCADA systems with a view to the future. SCADA technic is rarely used in construction field this paper is all about the SCADA technology used in construction industries like in RMC plant, HOT mix plant, Equipment‘s, irrigation districts, etc. The first ‗SCADA‘ systems utilized data acquisition by means of panels of meters, lights and strip chart recorders. The operator manually operating various control knobs exercised supervisory control. These devices were and still are used to do supervisory control and data acquisition on plants, factories and power generating facilities. The sensors are connected directly to the meters, switches and lights on the panel. This technology in advance technology which is one time investment for mass construction. In PWD (Public Work Department) SCADA technology has been made compulsory for road construction.